The influence of the feeding level of white-red belted pigs on the interior indicators - Флока, Л. В. (Scientific Progress & Innovations, 2016)
The influence of feeding white-red belted pigs on interior performance. An important step in pig breeding is to identify and develop criteria for predicting the performance of the animal at an early age for the interior design features. It speeds up the process of evaluating breeding value of animals and improving breeding work in the herd. Using interior performance of animals in breeding work with the herd indicates that today's pork industry makes increasing demands for higher genetic and biological quality in the pigs and their adaptability to conditions and feeding.